Cardiac psychoses: a study of the etiology, clinical features, and prognosis - Weinstein, Joseph (The University of Edinburgh, 1930)
1. Serious psychoses occurring as complications of heart disease are not common. 2. All the patients under observation had suffered from advanced and recurring heart failure, and the development of the confusional state coincided with the period of severe decompensation. So the exciting cause of these psychoses, or at least a constant factor in them, is the presence of advanced cardiac failure. 3. These mental disturbances are independent cf the type of heart affection. 4. All the patients were over forty years cf age. The greatest incidence occurred in the seventh, the least in the eighth decade of life. 5. Both sexes were equally affected. 6. It might be safe to assume that these psychoses are determined, in some cases at least, by inadequate nutrition of the brain and special centers consequent on the disordered circulation. 7. Generalized and cerebral arteriosclerosis are of decisive importance in some cases, at any rate. 8. High arterial blood pressure, with one exception, was common to all. 9. Digitalis poisoning may be held responsible in unusual cases for the development of a psychopathic outbreak. 10. Exhaustion from long standing heart disease is another important factor in the etiology of the cardiac psychoses. 11. The most important and frequent manifestations of these disorders are: (a) A state of mental confusion. (b) Hallucinations of sight, sound, and rarely of taste. (c) Delusions of persecution, rarely those of grandeur. (d) A state of excitation. (e) A depressive mood. (f) Insomnia - a constant symptom. 12. The occurrence of psychoses in patients with far advanced and recurring cardiac failure is of grave prognostic significance.